2009
DOI: 10.1017/s003329170900600x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced ‘Reading the Mind in the Eyes’ in borderline personality disorder compared to healthy controls

Abstract: Background Borderline personality disorder (BPD) is partly characterized by chronic instability in interpersonal relationships, which exacerbates other symptom dimensions of the disorder and can interfere with treatment engagement. Facial emotion recognition paradigms have been used to investigate the bases of interpersonal impairments in BPD, yielding mixed results. We sought to clarify and extend past findings by using the Reading the Mind in the Eyes Test (RMET), a measure of the capacity to discriminate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
213
13
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 263 publications
(258 citation statements)
references
References 44 publications
(87 reference statements)
25
213
13
2
Order By: Relevance
“…We also classified the stimuli used in the Eyes task into three emotional valence categories: positive (8 items), neutral (16 items) and negative (12 items), using the criterion of Yildirim et al (2011) and Fertuck et al (2009).…”
Section: Methodsmentioning
confidence: 99%
“…We also classified the stimuli used in the Eyes task into three emotional valence categories: positive (8 items), neutral (16 items) and negative (12 items), using the criterion of Yildirim et al (2011) and Fertuck et al (2009).…”
Section: Methodsmentioning
confidence: 99%
“…Consistent with some of the facial expression recognition research, Preißler et al (2010) argued that the higher sensitivity of the MASC reveals a reduction in the ability of individuals with BPD to integrate complex social information, especially when time is constrained. In contrast, Fertuck et al (2009) (2009) control group may have reduced control scores to a lower end of the range than is normally reported in control subjects, and therefore increased the probability of detecting group differences.…”
Section: Mentalization Using Passive Stimulimentioning
confidence: 85%
“…This general lack of study may be attributable in part to the questions of whether or not the phenomenon actually exists, and furthermore, if it can be clearly and reliably documented and explained. Recent studies have reported both enhanced (i.e., Fertuck et al, 2009;Franzen et al, 2011;Frick et al 2012) and impaired (i.e., Preißler, Dziobek, Ritter, Heekeren, & Roepke, 2010) social cognition in BPD, but the evidence for borderline empathy has yet to be comprehensively reviewed and evaluated in the context of alternative hypotheses for causation. In this article, we evaluate the existing evidence for enhanced empathy in BPD by systematically searching the literature and providing an overview of the relevant studies with consideration of their varying methodological approaches.…”
mentioning
confidence: 99%
“…Previous findings regarding empathy in BPD have been conflicting: some studies showed that patients exhibit less empathy compared to controls (Minzenberg et al, 2006;Preißler et al, 2010;Fertuck et al, 2009), while others found evidence for heightened empathy (Franzen et al, 2011;Dinsdale and Crespi, 2013) in patients. Although this conflicting pattern has been explained by referring to the different domains of empathy that show reduced cognitive empathy in BPD patients with unchanged or even heightened affective empathy (reviewed in Dinsdale and Crespi, 2013), here we found that even the affective domain of empathy may be reduced, possibly reflecting a compensatory response in order to protect from emotional contagion through the emotions of others that has been found in BPD (Dinsdale and Crespi, 2013).…”
Section: Discussionmentioning
confidence: 97%